Impact of malicious servers over trust and reputation models in wireless sensor networks. Issue 3 (3rd March 2016) - Verma, Vinod Kumar; Singh, Surinder; Pathak, N.P.
Abstract : This article deals with the impact of malicious servers over different trust and reputation models in wireless sensor networks. First, we analysed the five trust and reputation models, namely BTRM-WSN, Eigen trust, peer trust, power trust, linguistic fuzzy trust model. Further, we proposed wireless sensor network design for optimisation of these models. Finally, influence of malicious servers on the behaviour of above mentioned trust and reputation models is discussed. Statistical analysis has been carried out to prove the validity of our proposal.